ZnPd/ZnO Aerogels as Potential Catalytic Materials - Ziegler, Christoph; Klosz, Stefan; Borchardt, Lars; Oschatz, Martin; Kaskel, Stefan; Friedrich, Matthias; Kriegel, Rene; Keilhauer, Toni; Armbruester, Marc; Eychmueller, Alexander (Advanced Functional Materials, 2016)
Many different aerogel materials are known to be accessible via the controlled destabilization of the respective nanoparticle suspensions. Especially for applications in heterogeneous catalysis such materials with high specific surface areas are highly desirable. Here, a facile method to obtain a mixed ZnPd/ZnO aerogel via a reductive treatment of a preformed Pd/ZnO aerogel is presented. Different morphologies of the Pd/ZnO aerogels could be achieved by controlling the destabilization of the ZnO sol. All aerogels show a high CO2 selectivity of up to 96% and a very good activity in methanol steam reforming that delivers hydrogen, which is one of the most important fuels for future energy concepts. The method presented is promising for different transition metal/metal oxide systems and hence opens a path to a huge variety of materials.
CRIS-Team Scopus Importer:2023-03-20
Keywords: heterogeneous catalysis; intermetallic compound; methanol steam reforming; nanoparticle assembly; PdZn